2017
DOI: 10.1080/09638288.2017.1400596
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the current practice of intramuscular Botulinum toxin injections for hemiplegic shoulder pain in the UK

Abstract: Current UK practice of Botulinum Toxin type A injections for hemiplegic shoulder pain associated with spasticity is highly variable. There are large gaps between current practice and available evidence with regards to muscle selection and doses used. A number of areas for further investigation have been identified to progress current understanding of this intervention. Implications for rehabilitation There are wide variations in practice for this complex intervention and clinicians should consider that their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…The intramuscular injection of BTX‐A to the motor endplate or to the INDR to block muscle spasticity has become increasingly popular (Tang, Li, et al, 2018 ; Tang, Zhang, et al, 2018 ; Yang et al, 2017 ). Injecting BTX‐A to block the spasticity of the pectoralis major muscle is the most commonly used method to treat hemiplegic shoulder pain (Holmes & Connell, 2019 ). For the pectoralis minor muscle, BTX‐A injection can also treat outlet syndrome (Rahman et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The intramuscular injection of BTX‐A to the motor endplate or to the INDR to block muscle spasticity has become increasingly popular (Tang, Li, et al, 2018 ; Tang, Zhang, et al, 2018 ; Yang et al, 2017 ). Injecting BTX‐A to block the spasticity of the pectoralis major muscle is the most commonly used method to treat hemiplegic shoulder pain (Holmes & Connell, 2019 ). For the pectoralis minor muscle, BTX‐A injection can also treat outlet syndrome (Rahman et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to the best of our knowledge, INPUT is the first international survey characterizing a clinical training programme in order to assess its impact and identify improvement opportunities. The few survey results published describe general or local practices or a specific aspect of management (33)(34)(35)(36)(37)(38). Respondents are probably the most motivated to undertake training and innovative approaches, and the most involved in the Ixcellence Network R programme.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that long-term treatment could improve subjective symptoms of sleeplessness and arm weakness caused by sequelae of stroke without recovery of motor function in upper extremity, while also decreasing pain. BoNT-A treatment for sequelae after stroke has shown short-term therapeutic effects within 12 months [12,14,15,16]. Additionally, VAS is commonly used for pain assessment [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Injections are repeated approximately every three months to maintain the efficacy of BoNT-A. The recovery of motor paralysis of the upper extremity may take more than six months post-stroke patients, indicating that doses of BoNT-A would be needed for a longer period [11,12]. These effects were verified by research of repeated BoNT-A administration for up to one and half years [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%